DINAMIKA KOALISI PARTAI-PARTAI POLITIK DI INDONESIA MENJELANG DAN SETELAH PEMILIHAN PRESIDEN TAHUN 2014 - Sumadinata, R. Widya (Departemen Ilmu Politik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2016)
This paper examines the dynamics of a coalition of political parties in Indonesia, especially in the presidential election of 2014 through a Fuzzy approach. The results of this study indicate that the ideology of political parties cannot be used as coalition preferences in absolute terms. The formation of the coalition is heavily based on seeking office interest. In other words, political parties in Indonesia have not been able to gain funding independently but still rely on state resources that obtained through its members in the executive and legislative offices. However, fuzzy logic modeling to the coalition as conducted in this writing is still very simple and need to test rigor of mathematical models that can describe the real condition of the behavior of political parties to form a coalition.Â